'Why do we think we are doing everything right [just] because we do it': what transforms Chinese and Scottish student-teachers' taken-for-granted views in study abroad experiences. Issue 7 (3rd October 2022) - Li, Huaping; Costa, Cristina
ABSTRACT: This paper reports on how varied study abroad experiences transformed understanding of difference of student-teachers from two universities. Data were collected through a qualitative questionnaire and semi-structured interviews with 14 Chinese and Scottish student-teachers who presented what they had experienced and how they had made sense of difference. Drawing on transformative learning, this study reveals that opportunities to experience difference and resultant emotional struggles can develop student-teachers' emotional maturity and readiness for change. It also highlights that critical reflection on challenges in their preconceptions about the self and others is essential to transform their preconceived views and develop their openness to difference. To maximise the transformative potential of study abroad programmes, we argue that student-teachers must be provided with a discourse that disrupts their taken-for-granted views and learning opportunities that have a critical orientation.